Exploring The Use Of Artificial Intelligence Technology In Improving Personalization Of Product Marketing Strategies: A Case Study On The Automotive Industry - Bungkundapu, Osvaldo; Tayaya, Gabriel Natasya (Marcha Institute, 2023)
This research investigates the application of Data Privacy Compliance methods in improving the personalization of product marketing strategies using artificial intelligence technology in the automotive industry. With a focus on compliance with applicable data privacy regulations, this research explores the impact of such an approach on consumer satisfaction, marketing strategy effectiveness, and corporate reputation. The results show that prioritizing consumer privacy can bring significant benefits, including increased consumer trust, better risk management, and long-term competitive advantage. However, the research also identifies limitations in access to relevant data and limited time frames, and suggests conducting follow-up studies on the long-term effects of implementing this strategy, as well as exploring new challenges and opportunities that arise in the development of future research.